The crop–livestock–soil nutrient–water nexus in mixed farming system: a research gap in West Africa Region - Igbadun, H. E.; Ojeleye, O. A.; Mabhaudhi, T.; Cofie, Olufunke O. (Springer, 2025)
Mixed farming systems are a sustainable closed-loop model for crop–livestock systems, focusing on structure, practices, logic, social, cultural, economic, climatic, and institutional capital interactions. However, literature on crop–livestock–soil–water interactions is scarce, with few separating crop and livestock water productivity in mixed systems. Crop–livestock water productivity is influenced by land management, biophysical, and socioeconomic factors. Integrating thinking in space and time can help understand these interrelationships and analyse their influence on crop–livestock production. Improving livestock water productivity (LWP) is crucial due to rising consumer demand, competition for global freshwater, and water rivalry. Strategies include promoting livestock production, managing grazing, water, livestock marketing, animal health, and minimizing environmental effects.